Vulnerability functions for singapore flood risk - Low, Kum Theng. (2013)
In 16 June 2010, Singapore was shocked by the flash flood in Orchard Road. Soon after, Orchard Road and other parts of Singapore had been hit by flash floods. Due to these flooding events, properties and vehicles were damaged.